Challenges and Solutions in the Implementation of Digital Technology in MSMEs: Perspectives from Entrepreneurs and Consumers - Handayati, Ratna; Rozaq, Ahmad Syaifur; As'adi, Firman Nur; Saputra, Mohammad Zaky Dwi; Ubaidillah, Mochammad Miftachul (Technology and Society Perspectives (TACIT), 2024)
Technological advancements bring enormous benefits. Nonetheless, many MSMEs experience significant obstacles in the application of this technology. This research aims to provide a comprehensive literature review on the challenges faced by MSMEs in adopting digital technology and the solutions that can be implemented from both entrepreneurs' and consumers' perspectives. The study employs a literature review method with a qualitative approach and descriptive analysis. Research data were sourced from Google Scholar, covering publications from 2020 to 2024. The findings indicate that the implementation of digital technology in MSMEs in Indonesia encounters several significant challenges, including a lack of knowledge and technical skills, high implementation costs, and inadequate infrastructure. Other notable challenges include resistance to change, data security issues, misalignment of technology with the specific needs of MSMEs, and insufficient technical support and consultation. Nevertheless, various solutions can be applied to overcome these obstacles, such as enhancing education and training, providing financial incentives, improving infrastructure, offering technical support, and developing data security solutions. Real-world case studies of MSMEs like "Warung Sederhana," "Toko Sari Rasa," and "Kios Digital" illustrate the relevant challenges and solutions in the context of digital technology adoption.